Effectiveness of Intravenous Multimodal Analgesic Combination in Postoperative Pain Management in Breast Cancer Patients Undergoing Mastectomy with General Anesthesia: Systematic Literature Review - Maharani, Cindy; Suandika, Made; Purnawan, Heru (Sean Institute, 2025)
Post-mastectomy pain in breast cancer patients is a clinical problem that often has long-term effects, including the development of post-mastectomy pain syndrome (PMPS). The use of single opioids has limitations due to the risk of side effects and dependence, so intravenous multimodal analgesia approaches with various combinations of analgesic agents are increasingly being studied. This study aims to evaluate the effectiveness of multimodal intravenous analgesic combinations in controlling postoperative pain in breast cancer patients undergoing mastectomy with general anesthesia. A systematic review was conducted according to the PRISMA 2020 guidelines through searches in PubMed, Cochrane Library, ScienceDirect, and EBSCO for publications from 2005 to 2025. Articles that met the inclusion criteria were randomized controlled trials (RCTs) and cohort studies that assessed the effectiveness of multimodal intravenous analgesic combinations in mastectomy patients. The methodological quality was assessed using the Joanna Briggs Institute (JBI) instrument. A total of 11 studies involving more than 800 mastectomy patients were analyzed. The combination of pregabalin and esketamine was shown to significantly reduce the incidence of chronic pain up to 6 months post-surgery (14.3% and 7.1% vs. 46.3% and 31.7%; p<0.01), as well as reduce opioid consumption. Remifentanil–dexmedetomidine provided better analgesia while improving the patient's immunological profile. Ketamine-based anesthesia was more effective than opioids in reducing acute pain, while the combination of ketamine–magnesium sulfate was proven to be safe and opioid-sparing. The use of diclofenac reduced opioid consumption but increased the risk of bleeding, while intravenous lidocaine showed inconsistent results. The combination of multimodal intravenous analgesics is effective in optimizing pain control after mastectomy, reducing opioid consumption, and potentially preventing chronic pain. Adjusting the multimodal protocol according to the patient's profile is necessary to maximize benefits while minimizing the risk of side effects.